For the Temple: A Tale of the Fall of Jerusalem - Henty, G. A. (George Alfred), 1832-1902 (Salt Lake City, UT : Project Gutenberg, 2007)
"For the Temple: A Tale of the Fall of Jerusalem" by G. A. Henty is a historical novel written in the late 19th century. It narrates the dramatic and tumultuous events surrounding the fall of Jerusalem and the resistance against Roman rule, focusing on the life of a young boy named John, who is set against a backdrop of civil strife, patriotism, and impending doom. As the story unfolds, readers are likely to encounter themes of bravery, loyalty, and the tragic consequences of war. The opening of the tale introduces us to John, a thoughtful boy enjoying the serene beauty of Lake Tiberias, while his family busily harvests figs and grapes. Tension lurks beneath the surface as John's mother expresses concern that peaceful times may soon give way to trouble, hinting at the historical unrest in Galilee. As John helps gather figs, we also meet Mary, his cousin, who shares a playful bond with him. The stage is set for the larger conflict to come, as discussions of political unrest and impending warfare are foreshadowed by the characters' lively interactions and familial concerns. (This is an automatically generated summary.)
Release date is 2007-05-26
Produced by Martin Robb.
Keywords: War stories; Conduct of life -- Juvenile fiction; Soldiers -- Juvenile fiction; Jews -- Juvenile fiction; Romans -- Juvenile fiction; Temple of Jerusalem (Jerusalem) -- Juvenile fiction